Fueling electrification: The impact of gas prices on hybrid car usage - Laura Grigolon; Eunseong Park; Kevin Remmy (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We use micro-level data on fuel consumption, mileage, and travel mode to study plug-in hybrid drivers' response to fuel prices. When fuel prices rise, plug-in hybrids reduce fuel consumption more than gasoline and diesel cars. They do not reduce their mileage but increase electric recharging, without evidence of habit formation. As the share of kilometers driven in electric mode by plug-in hybrids is only half the official test cycle value, fuel prices are effective in improving the environmental performance of these vehicles. We estimate drivers' value of charging time at exteuro15 to exteuro41/hour.
Keywords: D12; L91; Q31; 330; fuel price elasticity; automobiles; carbon emissions